Physics-based modeling and information-theoretic sensor and settings selection for tool wear detection in precision machining. (September 2022) - Awasthi, Utsav; Wang, Zhigang; Mannan, Nasir; Pattipati, Krishna R.; Bollas, George M.
Abstract: Precision machining of metals is an energy intensive process with applications and impacts across the manufacturing industry. The energy efficiency, product yield, and maintenance of the precision machine require a digital twin that can assist with prognostics and health management. Here, a physics-based model is developed and validated against face milling data, and then used for the timely and precise inference of machining faults that cannot be measured directly. Computer numerical control (CNC) measurements of power and force are used through this physics-based machining model to predict deviations of the outputs of power consumption and cutting forces during normal operation. A model-based fault detection and isolation methodology is applied to determine the optimal (traditional and available) sensor suite and the test settings (admissible input values) that improve the inference of tool wear in face milling. The optimal sensor suite and input test settings are obtained by solving a mixed integer non-linear program that optimizes information-theoretic metrics relevant to the detection and isolation of tool wear from steady-state or transient machining measurements. Dynamic time warping and k —NN classification are then used to validate the robustness of the optimal design for fault detection test design, including the optimal sensor suite. Graphical abstract: Unlabelled Image